A Study on Wicking in Natural Staple Yarns - Q. Li; J. J. Wang; C. J. Hurren (Journal of Natural Fibers, 2017)
In this study, natural staple yarns of cotton and wool were investigated for wicking properties. Fibre packing density reflected by yarn wicking rates was measured in ply cotton yarns. It was seen that with the samples measured in this work, both twist level and number of ply in a yarn can affect yarn wicking behavior. When twist and yarn count remained unchanged, wool yarns with different fibre diameters were measured for wicking rates and the best wicking was found on the yarn with the coarsest fibre diameter. Comparison was made in this work on the treatment methods, and on both synthetic continuous filament yarns and the natural staple yarns. While prewash treatment could improve yarn wicking by changing fibre surface condition, plasma treatment was a more effective way in increasing yarn wicking rate for both filament yarns and staple yarns.